Violation of DNA neighbor exclusion principle in RNA recognition. Issue 6 (22nd February 2016) - Yousuf, Muhammad; Youn, Il Seung; Yun, Jeonghun; Rasheed, Lubna; Valero, Rosendo; Shi, Genggongwo; Kim, Kwang S.
Abstract : DNA intercalation has been very useful for engineering DNA-based functional materials. Abstract : DNA intercalation has been very useful for engineering DNA-based functional materials. It is generally expected that the intercalation phenomenon in RNA would be similar to that in DNA. Here we note that the neighbor-exclusion principle is violated in RNA by naphthalene-based cationic probes, in contrast to the fact that it is usually valid in DNA. All the intercalation structures are responsible for the fluorescence, where small naphthalene moieties are intercalated in between bases via π–π interactions. The structure is aided by hydrogen bonds between the cationic moieties and the ribose-phosphate backbone, which results in specific selectivity for RNA over DNA. This experimentally observed mechanism is supported by computationally reproducing the fluorescence and CD data. MD simulations confirm the unfolding of RNA due to the intercalation of probes. Elucidation of the mechanism of selective sensing for RNA over DNA would be highly beneficial for dynamical observation of RNA which is essential for studying its biological roles.